2018
DOI: 10.12659/msm.909098
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic Acid Improves Polycystic Ovary Syndrome in Rats via Sterol Regulatory Element-Binding Protein 1 (SREBP-1)/Toll-Like Receptor 4 (TLR4) Pathway

Abstract: BackgroundThis study aimed to investigate the protective effect of eicosapentaenoic acid (EPA) on rats with polycystic ovary syndrome (PCOS).Material/MethodsRats with PCOS were intraperitoneally injected with different doses of EPA. Levels of follicle stimulating hormone (FSH), luteinizing hormone (LH), and testosterone (T) were measured using corresponding kits. HE staining was used to observe lesions in ovarian tissue. Levels of inflammatory factors in ovarian tissue of rats were detected by ELISA. RT-PCR wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…We showed that BBR regulated the expression levels of TLR4 , LYN , NF-kB , TNF-α , IL-1 , and IL-6 caused by PCOS. TLR4 plays an important role in proinflammatory signaling and its levels are significantly higher in rats with PCOS compared to those without PCOS [ 28 ]. Further, TLR4 binds to its receptor and activates NF-kB to produce proinflammatory cytokines, including TNF-α , IL-1 , and IL-6 [ 11 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We showed that BBR regulated the expression levels of TLR4 , LYN , NF-kB , TNF-α , IL-1 , and IL-6 caused by PCOS. TLR4 plays an important role in proinflammatory signaling and its levels are significantly higher in rats with PCOS compared to those without PCOS [ 28 ]. Further, TLR4 binds to its receptor and activates NF-kB to produce proinflammatory cytokines, including TNF-α , IL-1 , and IL-6 [ 11 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study indicates that an intake of dietary EPA exerted beneficial effects on androgens in PCOS (62). Moreover, EPA treatment increases the number of follicular cell layers and decreased the levels of LH and T in PCOS (27).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary ALA-rich FO inhibited the production of TNF-α, IL-1β, and IL-6 in T2DM and ALD (37,38). EPA treatment can decrease IL-1β and TNF-α but increase IL-10 in PCOS (27). Clinical studies have shown that the supplementation of omega-3 PUFAs is beneficial in decreasing the MCP-1 expression in macrophages and the levels of endothelial chemokine (72,73).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the literature regarding TLR expression in patients with PCOS is scarce. Two studies presented data describing increased TLR4 in ovarian tissues from animal models of PCOS [54,55], and it has been reported that ovarian cumulus cells from women with PCOS presented an abnormal TLR expression [56]. Gonzalez et al [57,58] recently reported increased TLR2 expression in peripheral blood mononuclear cells in women with PCOS after ingestion of cream regardless of obesity, and a similar increase in TLR4 expression that occurred mostly in obese women with the syndrome.…”
Section: Discussionmentioning
confidence: 99%